The equalization of teachers salaries to other professionals with equivalent education level: an analysis of regional inequalities - Augusto Marques de Castro Oliveira; Mariano Laio de Oliveira; Alexandre José de Souza Peres; Geraldo Andrade da Silva Filho (Fineduca, 2015)
This paper aims to analyze the appreciation of public K-12 education teachers by means of the equalization of their average income to other professionals with equivalent educational level, the central axis of Target 17 of the National Education Plan (PNE). The article presents a brief overview of the average income of public school teachers in relation to other professionals, disaggregated by Federative Unit (UF), sex and race/skin color.